Ibn Taymiyya on Reason and Revelation A Study of Darʾ taʿāruḍ al-ʿaql wa-l-naql - Sharif El-Tobgui, Carl (Islamic Philosophy, Theology and Science. Texts and Studies, 2019)
In Ibn Taymiyya on Reason and Revelation, Carl Sharif El-Tobgui offers a comprehensive analysis of Ibn Taymiyya's ten-volume magnum opus, Darʾ taʿāruḍ al-ʿaql wa-l-naql, elucidating its author's foundational reconstitution of rationality through the multifaceted ontological, epistemological, and linguistic reforms he carries out. Readership: Students and scholars of Ibn Taymiyya or Islamic theology, philosophy, or rationalism; students and scholars of medieval Christian and Jewish scholasticism; general readers interested in questions of reason and revelation.